Penguatan Profil Pelajar Pancasila Melalui Pembelajaran Berbasis Aplikasi Thunkable di SMA Negeri 2 Kabupaten Sorong - Melda Agnes Manuhutu; Sherly Gaspersz; Lulu Jola Uktolseja; Martinus Martinus; Helena Helena; Delvi Delvi; Kartika Kartika; Titus Titus (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This community service activity addresses the growing need for adaptive education in the digital era by focusing on strengthening the character and competence of students in line with rapid technological developments. The Pancasila Student Profile, which serves as the foundation of the Merdeka Curriculum, outlines six core dimensions: faith and piety, global diversity, cooperation, independence, critical reasoning, and creativity. Among these, creativity, independence, and critical thinking are crucial for preparing students to become innovators and problem-solvers in the digital world. However, schools in developing regions often face limitations in implementing these dimensions due to lack of resources and digital literacy. This program was implemented at SMA Negeri 2 Sorong Regency with the objective of strengthening the Pancasila Student Profile by providing training in the use of Thunkable, a visual programming platform for creating drag-and-drop mobile applications. The activity used a Project-Based Learning (PjBL) approach, enabling students to actively engage in designing simple educational applications that align with their learning context. The method encouraged hands-on exploration, teamwork, critical analysis, and creative thinking. Throughout the training, students not only learned how to navigate the Thunkable platform but also developed functional mobile apps addressing real-life learning challenges. The outcomes of the program showed a marked improvement in students’ digital literacy, problem-solving ability, innovation, and collaboration. Furthermore, students began to view themselves not just as consumers of technology but as producers of meaningful digital solutions. This initiative demonstrates that integrating digital technology with project-based learning can effectively support the implementation of the Pancasila Student Profile, even in remote or underdeveloped areas. It provides evidence that with the right approach and tools, students can be empowered to become digitally literate, creative, and socially responsible individuals who are ready to act as agents of change in the 21st century.